2018
DOI: 10.1002/adsc.201800928
|View full text |Cite
|
Sign up to set email alerts
|

Isobutyl Nitrite‐Mediated Synthesis of Quinoxalines through Double C−H Bond Amination of N‐Aryl Enamines

Abstract: An efficient and metal-free double CÀH bond amination of N-aryl enamines using isobutyl nitrite (IBN) has been developed. This method enables the preparation of functionalized quinoxalines in good to excellent yields and tolerates a variety of N-aryl enamines with diverse functional substituents. Mechanistic studies revealed the presence of a key b-imino oxime ester intermediate. A quinoxaline derivative could be prepared from bcarbonyl ester in one-pot sequence on a gram scale. Finally, two important quinoxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Specifically, Zhang and colleagues in 2014 reported that N -aryl enamines could react with nitromethane through an oxidative tandem nitrosation/cyclization sequence enabled by the KI/TBHP catalytic system, furnishing the metal-free synthesis of 3-trifluoromethylquinoxalines in a single step with high efficiency (Scheme a) . In a related synthesis, Mo, Pan, Su, and their co-workers utilized readily available iso -butyl nitrite (IBN) as a novel nitrogen reagent to construct C–N bonds and reported on a reaction between N -aryl enamines and IBN in the presence of Ac 2 O (Scheme b) . This process presumably involved the generation of the key β-imino oxime ester intermediate and subsequent 6πe-azacyclization.…”
Section: Alkenyl C–h Bond Functionalization Of Alkenes Containing a H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Zhang and colleagues in 2014 reported that N -aryl enamines could react with nitromethane through an oxidative tandem nitrosation/cyclization sequence enabled by the KI/TBHP catalytic system, furnishing the metal-free synthesis of 3-trifluoromethylquinoxalines in a single step with high efficiency (Scheme a) . In a related synthesis, Mo, Pan, Su, and their co-workers utilized readily available iso -butyl nitrite (IBN) as a novel nitrogen reagent to construct C–N bonds and reported on a reaction between N -aryl enamines and IBN in the presence of Ac 2 O (Scheme b) . This process presumably involved the generation of the key β-imino oxime ester intermediate and subsequent 6πe-azacyclization.…”
Section: Alkenyl C–h Bond Functionalization Of Alkenes Containing a H...mentioning
confidence: 99%
“…637 In a related synthesis, Mo, Pan, Su, and their coworkers utilized readily available iso-butyl nitrite (IBN) as a novel nitrogen reagent to construct C−N bonds and reported on a reaction between N-aryl enamines and IBN in the presence of Ac 2 O (Scheme 393b). 638 This process presumably involved the generation of the key β-imino oxime ester intermediate and subsequent 6πe-azacyclization.…”
Section: Enaminesmentioning
confidence: 99%
“…To confirm the presence of singlet oxygen, control experiments were carried out in the presence of 2.0 equiv. of 1 O 2 scavengers such as DABCO (1,4-diazabicyclo[2.2.2]octane), 26 TEMP (2,2,6,6-tetramethylpiperidine) 26 and NaN 3 27 under identical conditions as shown in Scheme 3. The formation of only a trace amount of the oxazole product 3a in all cases confirms the importance of singlet oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new methods have been developed for the synthesis of quinoxaline derivatives. Diverse functionalized quinoxalines have been synthesized by the reaction of aryl amines with β‐keto oximes or double C−H bond amination of N ‐aryl enamines using isobutyl nitrite (IBN) …”
Section: Introductionmentioning
confidence: 99%